Haplogroup Prediction Using Y-Chromosomal Short Tandem Repeats in the General Population of Bosnia and Herzegovina - Babić Jordamović, Naida; Kojović, Tamara; Dogan, Serkan; Bešić, Larisa; Salihefendić, Lana; Konjhodžić, Rijad; Škaro, Vedrana; Projić, Petar; Hadžiavdić, Vesna; Ašić, Adna; Marjanović, Damir (Frontiers in Genetics, 2021)
Human Y-chromosomal haplogroups are an important tool used in population genetics and forensic genetics. A conventional method used for Y haplogroup assignment is based on a set of Y-SNP markers deployed, which exploits the low mutation rate nature of these markers. Y chromosome haplogroups can be successfully predicted from Y-STR markers using different software packages, and this method gained much attention recently due to its labor-, time- and cost-effectiveness. The present study was based on the analysis of a total of 480 adult male buccal swab samples collected from different regions of Bosnia and Herzegovina. Y haplogroup prediction was performed using Whit Athey's Haplogroup Predictor, based on haplotype data on 23 Y-STR markers contained within the PowerPlex® Y23 kit. The results revealed the existence of 14 different haplogroups, with I2a, R1a and E1b1b being the most prevalent with frequencies of 43.13%, 14.79% and 14.58%, respectively. Compared to the previously published studies on Bosnian-Herzegovinian population based on Y-SNP and Y-STR data, this study represents an upgrade of molecular genetic data with a significantly larger number of samples, thus offering more accurate results and higher probability of detecting rare haplogroups.